2013
DOI: 10.1002/mnfr.201300409
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenols in the treatment of age‐associated diseases: Revealing the pleiotropic effects of icariin by network analysis

Abstract: Polyphenols are a broad class of compounds. Some are ingested in substantial quantities from nutritional sources, more are produced by medicinal plants, and some of them are taken as drugs. It is becoming clear, that a single polyphenol is impacting several cellular pathways. Thus, a network approach is becoming feasible, describing the interaction of a single polyphenol with cellular networks. Here we have selected icariin to draw a prototypic network of icariin activities. Icariin appears to be a promising d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 155 publications
(180 reference statements)
1
28
0
Order By: Relevance
“…Icariin treatment also accelerated the transition from telogen to anagen phase in dorsal vellus hairs. Our result is consistent with those of previous studies, which demonstrated that icariin treatment increases IGF‐1 mRNA expression in animal models …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Icariin treatment also accelerated the transition from telogen to anagen phase in dorsal vellus hairs. Our result is consistent with those of previous studies, which demonstrated that icariin treatment increases IGF‐1 mRNA expression in animal models …”
Section: Discussionsupporting
confidence: 94%
“…Icariin has demonstrated extensive pharmacological activities, including anti‐angiogenesis, anti‐oxidant, anti‐inflammatory and immunoprotective activity . Moreover, icariin has been identified as being involved in the regulation of multiple genes . For example, some studies have shown that icariin treatment can increase the mRNA expression of IGF‐1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include interaction with transition metals, inactivation of free radicals, inhibition of inflammatory response, modulation in the activity of different enzymes, and effects on intracellular signaling pathways and gene expression [5,16]. They are natural antioxidants and are thought to play a role in the prevention and treatment of several diverse conditions [18]. Some of these conditions include obesity, diabetes, osteoporosis, kidney and liver degeneration, cardiopathies, and geriatric diseases including AD [18].…”
Section: Introductionmentioning
confidence: 99%
“…There are two main processes typical of polyphenols that interest AD's development: antioxidation and anti‐inflammation mechanisms, which are the two main processes involved in the aging mechanism [1]. Polyphenols are considered to have a protective effect against inflammatory mechanisms and as such have been linked to AD, as to many other chronic diseases including diabetes, metabolic syndrome, and atherosclerosis [18].…”
Section: Introductionmentioning
confidence: 99%